Evaluation of nomophobia and related factors in high school students - TOPUZOĞLU, AHMET (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2020)
Objective: The aim of the study is to evaluate the 'nomophobia' which is determined as fear of being without access to cell phone, among high school students. Methods: This cross-sectional study was done on December 21st, 2018 in Besiktas at an Anatolian High School with the ethical committee and administrative approvals. In this study, the minimum sample size was 268 among 878 students, and 307 have been reached. Every grade in the school accepted as a stratum. Participants were chosen due to the population of each stratum. The survey was including 29 question, which contains a nomophobia scale valid in Turkish, and seven multiple-choice, two open-ended questions were used. Chi-square test and multiple linear regression analysis were done for data analysis and p<0.05 value accepted significant. %5 were used for standard deviation of prevalence and 95% for the confidence interval. Results: 52.8% of participants were female, %47.2 were male. 25.7% of the participants were 9th, 27.0% were 10th, 19.9% were 11th, 27.4% were 12th grade. 45.3% of participants' fathers and 42.3% of mothers had college degree. All participants had nomophobia with different levels of severity due to defined criteria; 48.5% of participants had mild, 45.6% had moderate, 5.9% had severe nomophobia. Mothers' and fathers' education level have no impact on nomophobia. Most participants were using their phones 2-4 hours per day (48.5%). Nomophobia is significantly high among long-hour-users. 77% were using the phone for social media. They have significantly higher nomophobia. 48.0% were checking their phone when they woke up, this group had significantly higher nomophobia. 44.0% of participants had 3-6 actively used applications. Nomophobia severity had a significant relationship with the number of applications in cell phones. Discussion: In the research population all students have nomophobia. Consequently, understanding psychologic reasons and awareness related to nomophobia should increase for its prevention.
Keywords: phone; phobia; adolescents; school; student; addiction; social media